2020
DOI: 10.1007/s43032-020-00192-9
|View full text |Cite
|
Sign up to set email alerts
|

Serum Decorin and Biglycan as Potential Biomarkers to Predict PPROM in Early Gestation

Abstract: Preterm birth is a leading cause of neonatal mortality in the US and globally, with preterm premature rupture of fetal membranes (PPROM) accounting for one third of preterm births. Currently no predictive diagnostics are available to precisely assess risk and potentially reduce the incidence of PPROM. Bigycan and decorin, the main proteoglycans present in human fetal membranes, are involved in the physiological maturation of fetal membranes as well as in the pathophysiology of preterm birth. The serum protein … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
10
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 7 publications
(10 citation statements)
references
References 44 publications
0
10
0
Order By: Relevance
“…Through complex interactions involving TLR2/4 and NADPH oxidases (NOX), BGN influenced the synthesis and maturation of IL-1β [ 144 ]. The proinflammatory role of BGN deserves investigation, when considering the impact of inflammation in pregnancy [ 133 , 145 ].…”
Section: Mode Of Action Of Bgnmentioning
confidence: 99%
See 2 more Smart Citations
“…Through complex interactions involving TLR2/4 and NADPH oxidases (NOX), BGN influenced the synthesis and maturation of IL-1β [ 144 ]. The proinflammatory role of BGN deserves investigation, when considering the impact of inflammation in pregnancy [ 133 , 145 ].…”
Section: Mode Of Action Of Bgnmentioning
confidence: 99%
“…While serum DCN levels alone could predict PTB before 37th gestational week among preterm labor patients, a combined measurement with cervical length was required to predict PTB within 7 days and before the 34th gestational week [ 161 ]. PPROM was associated with lower DCN serum levels appearing in the second trimester [ 145 ] and a decline in p-Smad-2 [ 134 ]. As a possible cause of PPROM [ 68 , 162 , 163 ], chorioamnionitis was linked to substantial DCN degradation in the amnion [ 160 ].…”
Section: Role Of Dcn In Pregnancy-associated Disordersmentioning
confidence: 99%
See 1 more Smart Citation
“…Underhill et al ( 93 ) recently described a serum panel comprising two proteoglycans, i.e. biglycan and decorin, together with serum protein sex hormone-binding globulin (SHBG) as a promising second-trimester prenatal serum screening-based biochemical model with an ability to predict pPROM in asymptomatic women.…”
Section: Emerging Markers For Predicting Pprom and Chorioamnionitis In Women With Pprommentioning
confidence: 99%
“…biglycan and decorin, together with serum protein sex hormone-binding globulin (SHBG) as a promising second-trimester prenatal serum screening-based biochemical model with an ability to predict pPROM in asymptomatic women. They found that the increased serum concentrations of biglycan in conjunction with decreased serum concentrations of decorin and SHBG in the second trimester were observed in asymptomatic patients who developed pPROM later on ( 93 ). However, more scientific research is required to target effective screening strategies for PROM at term and preterm.…”
Section: Emerging Markers For Predicting Pprom and Chorioamnionitis In Women With Pprommentioning
confidence: 99%